Somali and the forest spirit. 4 - Gureishi, Yako (Titan Comics, 2025)
"The heartwarming journey of Somali and her Golem father continues as they venture deeper into the Edgelands in search of other humans. This volume introduces enchanting new encounters and settings, including a delightful evening of baking in a woodpecker's cozy cabin and a memorable reunion in Chompers' Row. Each step in their adventure not only brings them closer to their goal but also deepens their bond!"--Provided by publisher.